Supplementary datasets to the article "Patch exploitation behaviour by a parasitoid of a forest pest: The influence of host cues and intra- and interspecific interactions" (Ecological Entomology) [Conjunto de datos] - Suans Giorgi, Melisa Andrea (2023)
This research was funded by Consejo Nacional de Investigaciones Científicas y Técnicas (PIP 11220130100730) and Agencia Nacional de Promoción Científica y Tecnológica (PICT 2014-527).